Medium-Chain Triglycerides (MCTs) for the Symptomatic Treatment of Dementia-Related Diseases: A Systematic Review - Nike Meer; Tobias Fischer (Journal of Nutrition and Metabolism)
Pathomechanisms of dementias involve increasing damage to neuronal energy metabolism, resulting in degeneration-related insulin resistance and glucose hypometabolism. In this case, ketone bodies can provide an alternative energy source. Supplementation with medium-chain triglycerides (MCTs), which can induce ketogenesis, may alleviate brain energy deficits and improve neuronal function. This review aims to determine the effectiveness of MCT as a symptomatic treatment approach. The systematic literature search was conducted in April 2023 following the Cochrane Handbook and PRISMA guidelines. A total of 21 studies were included, comprising eight uncontrolled trials and 13 RCTs investigating the effects of MCT on Alzheimer’s disease (AD) and mild cognitive impairment (MCI). A substantial increase in plasma ketone levels and brain metabolic rates was observed. Cognitive assessments showed only occasional or domain-specific performance improvements. The effects on functional abilities or psychological outcomes have been inadequately studied. Besides gastrointestinal side effects, no harmful effects were observed. However, the evidence was severely weakened by heterogeneous and poorly designed study protocols, bias, and conflicts of interest. In conclusion, the ketogenic properties of MCTs may have beneficial effects on brain metabolism in AD and MCI but do not always result in measurable clinical improvement. Current evidence is insufficient to recommend MCT as a comparable symptomatic treatment option.